2020
DOI: 10.3389/fonc.2020.00541
|View full text |Cite
|
Sign up to set email alerts
|

Cell Reversal From a Differentiated to a Stem-Like State at Cancer Initiation

Abstract: Even if the Somatic Mutation Theory of carcinogenesis explains many of the relevant experimental results in tumor origin and development, there are frequent events that are not justified, or are even contradictory to this widely accepted theory. A Cell Reversal Theory is presented, putting forward the hypothesis that cancer is originated by reversal of a differentiated cell into a non-differentiated stem-like state, by a change of its intrinsic epigenetic state, following a perturbation on the cell and/or its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
(53 reference statements)
1
35
0
1
Order By: Relevance
“…In solid tumor, cancer cells exist in different states of differentiation and this can be expressed by the cell surface markers in various tumors. 11,12 Cancer stem cell theory states that a small subset of cells within a tumor characterized by stem-like properties can lead to tumor initiation, progression, and metastases. The self-renewing and differentiating capacity of CSC are responsible for tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumor, cancer cells exist in different states of differentiation and this can be expressed by the cell surface markers in various tumors. 11,12 Cancer stem cell theory states that a small subset of cells within a tumor characterized by stem-like properties can lead to tumor initiation, progression, and metastases. The self-renewing and differentiating capacity of CSC are responsible for tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The present hypothesis has many contact points with the Tissue Organization Field Theory (TOFT) 32 , 33 , in the sense that it considers cancer a disease of tissue organization, and a tumor can originate from a perturbation on the tissue environment, not of a single or reduced number of cells, leading to a transition from normal to pluripotent like cells 34 . The bioelectrical communication is then a mechanism for tissue cells homeostasis but also, in case of a major perturbation, a process driving a global cells’ state change.…”
Section: Bioelectric Bistability and Carcinogenesismentioning
confidence: 99%
“…In some tumors, noncancer cells can even dedifferentiate into cells with a stem-cell phenotype, forming the dedifferentiated cancer cells [19,20]. Although the circumstances in which the dedifferentiation occurs are not completely clear, it has been reported that stress, wounding, or hypoxia can be responsible for this process [21]. Moreover, it has been hypothesized that the dedifferentiation of noncancer cells in cells with stem-cell phenotype could represent a further event for tumor initiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the circumstances in which the dedifferentiation occurs are not completely clear, it has been reported that stress, wounding, or hypoxia can be responsible for this process [21]. Moreover, it has been hypothesized that the dedifferentiation of noncancer cells in cells with stem-cell phenotype could represent a further event for tumor initiation [21]. Stem-cell phenotypes in cancer can also be derived from paracrine effects from other cells; for example, endothelial cells can induce the CSC phenotype of human colorectal cancer cells by secreting factors promoting the CSC phenotype and Notch activation [22].…”
Section: Introductionmentioning
confidence: 99%